ANALISIS FUNGSI, KATEGORI DAN PERAN SINTAKSIS PADA TEKS DESKRIPSI DALAM SURAT KABAR HARIAN DETIK.COM - Anis Fathu Saadah; Meinisa Armila; Najwa Arfa Mulyasa; Iis Lisnawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to analyze the syntactic functions, grammatical categories, and semantic roles in the descriptive text titled “Ruang Tamuku yang Mungil” published on the news website detik.com. The study employs a qualitative descriptive method, with data collected through literature review and document analysis. The data were analyzed by identifying syntactic functions (subject, predicate, object, complement, and adverbial), grammatical categories (nominal phrase, verbal phrase, adjectival phrase, and prepositional phrase), and the semantic roles that emerge in the sentences.The findings indicate that from the fourteen sentences analyzed, there are variations in sentence structures such as P–S–K, S–P–Pel, S–P–O, K–P–S, and more complex structures like P–S–K–Pel and compound sentences containing clauses in the forms of S–P–O and S–P–K. Subjects in the sentences are generally in the form of nominal phrases (FN), while predicates consist of verbs (V), verbal phrases (FV), and adjectival phrases (FAdj), functioning to express existence, condition, or action. Objects and complements also tend to appear as FN or FAdj, and serve semantic functions such as agent, attribute, location, instrument, or existence. These findings show that the descriptive text presents relatively varied but patterned sentence structures, with a dominance of S–P–Pel and P–S–K. Semantically, the sentences in the text emphasize functions of existence, identification, and descriptive-attributive meaning, which reinforce the visual image of the living room as the object of description.The diversity of sentence structures, categories, and functions enriches insights, especially the repertoire of syntax in Indonesian